2015
DOI: 10.3109/08820139.2015.1009546
|View full text |Cite
|
Sign up to set email alerts
|

SulfatedRadix Cyathulae officinalisPolysaccharides Act as Adjuvant via Promoting the Dendritic Cell Maturation and Suppressing Treg Frequency

Abstract: This study was conducted to evaluate the adjuvant potential of sulfated Radix Cyathulae officinalis Kuan polysaccharides (sRCPS) and their effects on specific cellular and humoral immune responses to hepatitis B subunit vaccine in mice. Our data demonstrated that sRCPS significantly promoted the rHBsAg-specific IgG, IgG1, IgG2a, and IgG2b antibody titers, the activities of natural killer cells (NK) and cytotoxic T lymphocytes (CTL), T cells proliferation, and phagocytic capacity of peritoneal macrophages. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The maturation and activation of DCs is a key step to initiate the antigen-specific immune responses. Treg cells are a subgroup of T lymphocytes with immunosuppression and regulation function [ 43 ]. To understand the mechanism of AEAR enhancing V-induced immunity, we investigated the maturation of DCs and the number of Treg cells in spleen in immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…The maturation and activation of DCs is a key step to initiate the antigen-specific immune responses. Treg cells are a subgroup of T lymphocytes with immunosuppression and regulation function [ 43 ]. To understand the mechanism of AEAR enhancing V-induced immunity, we investigated the maturation of DCs and the number of Treg cells in spleen in immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…The serum was collected 14d after the booster vaccination, and the FMDV-specific IgG titer and IgG isotypes were measured using the indirect double-antibody sandwich enzyme-linked immunosorbent assay (ELISA) as described previously [ 57 , 58 ]. The optical density (OD) was measured by an ELISA reader (Model 680, Bio-Rad, Philadelphia, PA, USA) at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported bioactivity of some members of this genus. Cyathula officinalis Kuan (COK) contain polysaccharides which could increase mouse red cell immunity function by strengthening red cell immune adherence and cleanup of circulating immune complex [17], increase both cellular and humoral immune responses via up-regulating Dendritic cells maturation and suppressing the frequency of Treg cells [18,19]. COK whose root is a commonly-used traditional Chinese herbal medicine with a wide range of pharmacological activities [20,21,22] has also demonstrated antitumor activity.…”
Section: Introductionmentioning
confidence: 99%